2012
DOI: 10.1155/2012/317592
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Heterotopic Pregnancy Using Ultrasound and Magnetic Resonance Imaging in the First Trimester of Pregnancy: A Case Report

Abstract: Heterotopic pregnancy is a condition characterized by implantation of one or more viable embryos into the uterine cavity while another one is implanted ectopically, particularly into the uterine tube. Its occurrence has increased drastically over the last few years due to assisted reproduction procedures. In general, the diagnosis is made during the first trimester by using endovaginal two-dimensional ultrasound (2DUS), through observing a complex para- or retrouterine mass in association with a viable uterine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 4 publications
1
30
0
8
Order By: Relevance
“…It has been suggested that a delay in diagnosis can cause maternal mortality of 1% and foetal mortality of 45-65% [2]. It is important to perform a meticulous pelvic sonography evaluation to detect HP even in cases with a positive pregnancy test and an intrauterine gestational sac on sonography after infertility treatment [1]. Diagnosis of a HP can be challenging and a high index of suspicion is mandatory for early diagnosis and appropriate treatment.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been suggested that a delay in diagnosis can cause maternal mortality of 1% and foetal mortality of 45-65% [2]. It is important to perform a meticulous pelvic sonography evaluation to detect HP even in cases with a positive pregnancy test and an intrauterine gestational sac on sonography after infertility treatment [1]. Diagnosis of a HP can be challenging and a high index of suspicion is mandatory for early diagnosis and appropriate treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Gestational age, findings of transvaginal sonography, treatment modalities used and outcomes of pregnancy in cases. In cases of HP with tubal localisation, patients can present with acute abdomen and hypovolemic shock secondary to tubal rupture [1]. In such cases, the differential diagnosis includes a haemorrhagic corpus luteum cyst, adnexal torsion, a neoplasm and abortion [1,2].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations